Vázquez-Cano, E. (2021). Diseño de Unidades Didácticas en Primaria, Secundaria y Bachillerato. Octaedro Editorial - Flores Bravo, Ivonnia Marcela (2022)
Fil: Flores Bravo, Ivonnia M. Pontificia Universidad Católica Argentina; Argentina